Kinematic comparison of the overgrip and undergrip dismount gigant swings on the uneven bars - Prassas, S.; Papadopoulos, C.; Krug, J. (1998)
INTRODUCTION: Uneven bar dismounts are executed from either overgrip or undergrip giant swings. Gymnasts performing either of these two styles of dismounts attempt to optimize release conditions by incorporating a beat swing associated with hip joint motion. The purpose of this study was to quantify projectile determinants, and swing and beat characteristics of the overgrip and undergrip dismount giant swings on the uneven bars. METHODS: Thirteen (seven undergrip and six overgrip) giant swings, were recorded during the 1994 World Gymnastics Championships (Dortmund, Germany) with 2 video cameras operating at 50 Hz. They were analyzed utilizing the Ariel Performance Analysis System (APAS). Three dimensional position data of 12 body points (ankles, knees, hips, shoulders, elbows, and hands) and a point on the top bar were digitally smoothed before being submitted to further analysis. RESULTS: Results showed no significant differences between overgrip and undergrip dismount giant swings in terms of center of mass (CM) maximum and release angular velocities, CM position, and CM horizontal and vertical release velocities. Radius of gyration at release, reflecting body configuration, was significantly different (51.6 vs. 58.8 % of height for undergrip and overgrip dismount giants, respectively; p<.05). There were significant differences in the mechanics of the beat swing in terms of both magnitude of hip joint range of motion (111 vs. 65 degrees for undergrip and overgrip dismount giants, respectively; p<.001), and timing of the beat swing (starting in the first quadrant for the overgrip and second quadrant for the undergrip dismount giants; p<.001 and finishing in the second quadrant for the overgrip and third quadrants for the undergrip dismount giants; p<.001). CONCLUSION: Results indicate that overgrip and undergrip giant swings generated similar projectile determinants for uneven bars dismounts. There were, however, significant differences between the two swings in the timing and magnitude of the hip joint beat action which partially generates the projectile determinants. Even: http:// www.isbs98.uni-konstanz.de/Abstracts/Prassas4.PDF